THE EXCLUSION OF ETHICS - Standish, Paul (Bordón. Revista de Pedagogía, 2017)
INTRODUCTION. This paper focuses especially on what has been called the fragmentation of ethics in the university – the pigeonholing of ethical questions in such a way that ethics is deprived of its critical purpose and its practical possibilities are curtailed. At its worst, the understanding of ethics in this way takes it to be a “bolt-on” component to curricula, with citizenship education a further tokenistic addition, alongside entrepreneurial and ICT skills. Where ethics is addressed more systematically, problems of a different order arise. Quite commonly — for example, in courses in medical ethics — the trend has been to outline the “major ethical positions” (utilitarianism and deontology) and to invite learners to choose between them, exploring how each is best “applied” to particular cases in a field that is otherwise understood in technical terms. The prevailing ethos is one of what works best, and this is conceived against background assumptions of more or less uncontroversial ends. This paper is against ethics understood in these ways. It asks how can there be any subject of university study, in fact any university at all, without some sense of the value of that subject’s content or of what the institution is about. METHOD. This is a philosophical enquiry, and its methodological approach is that of the essay — that is, an unsystematic exploration of the topic, a trying-out of ideas in relation to its central theme. It does this through assembling the views of a number of highly influential thinkers and through engaging with those views. RESULTS. It affirms the multiple ways in which values inhere across the range of human practice. The university, rightly conceived, becomes the place where those values, especially those by which a society orients itself, are questioned and tested in an exemplary manner. DISCUSSION. It calls into question prominent ways of formulating questions about the ethical, suggesting that the confusions that abound around this notion stem in part from problems in moral philosophy. It seeks to articulate a better way of addressing these matters and of thinking ethically.